TYPICAL EARTHQUAKES OF BEREGOVO SEISMIC ZONE: FEATURES OF SOURCE AND MACROSEISMIC FIELD - NAZAREVYCH, L.; NAZAREVYCH, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
On example of one of typical earthquakes of Beregovo seismic area in Transcarpathians – Beregovo earthquake in 1965 the peculiarities of his source, of processes in him and of frequency composition of seismic radiation and also peculiarities of attenuation of macroseismic field of this earthquake are analyzed.